2020
DOI: 10.1002/ardp.201900299
|View full text |Cite
|
Sign up to set email alerts
|

Isatin dimers and their biological activities

Abstract: Dimerization is a promising strategy to develop novel drug candidates that could extend the biological spectrum, enhance the activity, overcome drug resistance, as well as improve pharmacological, pharmacokinetic, and physicochemical profiles. Isatin dimers possess a broad spectrum of biological properties and the isatin dimer indirubin has already been used in the clinic, revealing the potential of isatin dimers as putative drugs. This review covers the recent advances of isatin dimers as pharmacologically si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 90 publications
0
12
0
Order By: Relevance
“…Although a number of reviews on the synthesis and biological applications of isatins have recently appeared [ 8 , 9 ], the current review’s goal is to keep readers up to date on the biological applications of isatin derivatives and isatin hybrids, with a focus on cancer and Neglected Tropical Diseases such as malaria, tuberculosis, bacterial infections, and parasitic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of reviews on the synthesis and biological applications of isatins have recently appeared [ 8 , 9 ], the current review’s goal is to keep readers up to date on the biological applications of isatin derivatives and isatin hybrids, with a focus on cancer and Neglected Tropical Diseases such as malaria, tuberculosis, bacterial infections, and parasitic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…As a representative of the class of privileged structures, isatin and its derivatives are widely used in medicinal chemistry [1,2]. The progressing number of works on synthetic procedures [3] and the studies of this heterocycle push researchers in this area to publish generalized data on one or another type of biological activity [4][5][6][7]. It is due to the manifestation of isatin and its derivatives of a wide spectrum of activity, such as anti-cancer [8][9][10], anti-tubercular [11,12], antibacterial [13], anti-COVID [14,15], fungicidal [16,17], etc (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Being a member of the ‘privileged structure’ class, the isatin heterocyclic platform is widely used in pharmaceutical chemistry [10,11] Numerous studies have shown that derivatives of this heterocycle exhibit various types of biological activity, such as antiviral, antifungal, antibacterial, antiproliferative, antitumor, etc [12–19] . However, the usually low solubility of these compounds in biocompatible solvents does not allow more detailed studies of other types of their activity.…”
Section: Introductionmentioning
confidence: 99%